MULTRAN: a finite difference, multi-species, three-dimensional contaminant transport model - Waldron, Brian Anthony, author; Warner, James W., advisor; Afifi, Sameh, advisor (Colorado State University. Libraries, 1999)
Ground water contamination occurs since nothing is perfectly sealed or always environmentally safe. To return ground water systems to their previous state before contamination, remediation is necessary. Tools to aid agencies and environmental contractors to determine contaminant migration and its fate are available in many different forms such as analytical solutions, numerical models, and laboratory experiments. As there are a number of tools to study ground water contamination, so there are a number of numerical models for analyzing contaminant migration and its fate. Popular contaminant transport models, such as MT3D, are used widely for single species transport. However, ground water chemistry and/or multiple species can sometimes affect the transport of contaminants. Though models exist that can handle multi-species transport, an easy to understand model that also connects to the extremely popular ground water model, MODFLOW, does not exist. Therefore, the multi-species, three-dimensional, contaminant transport model, MULTRAN, is developed to fill this need. MULTRAN is a finite difference model that can simulate the stress packages associated with MODFLOW, capable of handling single species transport akin to MT3D, and handle multi-species transport. Verification of MULTRAN's numerical code and contaminant transport modeling capability is conducted for one-, two-, and three-dimensional systems. In all cases, MULTRAN matches the analytical solutions well. Though single species transport is possible with MULTRAN, the main thrust of this study is the modeling of multi-species transport. To show this multi-species capability and its significance in contaminant transport, an example case study involving remediation of a contaminated site is conducted. Clearly, the adding of a competing species that can be used to drive off contaminants from the soil matrix will aid and expedite the cleanup process. MULTRAN's multi-species capability indicates this procedure to be true. Therefore, MULTRAN allows modelers a greater freedom in modeling contaminated ground water systems due to its multi-species capability.
Keywords: civil engineering; hydrology; geochemistry; hydrologic sciences